2002
DOI: 10.1007/s00125-002-0805-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment and killing of human beta cells by enteroviruses: the capacity is shared by a wide range of serotypes, but the extent is a characteristic of individual virus strains

Abstract: Aims/hypothesis. Direct infection of beta cells could explain the diabetogenic effect of enteroviruses. Primary adult human beta cells are susceptible to coxsackievirus infections, which could result in impaired beta-cell function or cell death (coxsackieviruses B3, B4, B5) or both, or no apparent immediate adverse effects (coxsackievirus A9). We extended these studies to additional enterovirus serotypes including several echoviruses, some of which have been associated clinically with the development of Type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 35 publications
7
104
0
Order By: Relevance
“…On the other hand, during true virus infection of islets in nature, the infection may also induce changes in non-beta cell genes that may be relevant in the pathogenesis of type 1 diabetes mellitus. CBV-5 was selected out of more than 65 enterovirus serotypes capable of infecting humans, based on our previous results indicating that this prototype strain is one of the most destructive serotypes primarily infecting human beta cells [13,14] and on epidemiological studies supporting an association between CBV-5 infection and type 1 diabetes [10,30,31]. Because of space limitations, only some of the genes shown in Tables S2 and S3 are discussed here; additional information on some of these genes can be found in our previous publications dealing with microarray analysis of rat beta cells [28,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, during true virus infection of islets in nature, the infection may also induce changes in non-beta cell genes that may be relevant in the pathogenesis of type 1 diabetes mellitus. CBV-5 was selected out of more than 65 enterovirus serotypes capable of infecting humans, based on our previous results indicating that this prototype strain is one of the most destructive serotypes primarily infecting human beta cells [13,14] and on epidemiological studies supporting an association between CBV-5 infection and type 1 diabetes [10,30,31]. Because of space limitations, only some of the genes shown in Tables S2 and S3 are discussed here; additional information on some of these genes can be found in our previous publications dealing with microarray analysis of rat beta cells [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, cultured primary human beta cells are highly susceptible to infections caused by several enterovirus serotypes, representing different genetic subgroups and known to act through a number of different receptor families [9]. Of note, even the most cytolytic enterovirus strains kill beta cells only after several days in culture [13,14], suggesting a role for cytokines or other secondary virus-induced factors in the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological significance of enterovirus tropism has been demonstrated by the highly specific nature of the motorneuron damage in poliomyelitis, and it is possible that viral tropism could also explain the specificity of ␤-cell damage in type 1 diabetes. In vitro studies have shown that enteroviruses infect ␤-cells easily and induce functional impairment and cell death (49,50). Such a capacity seems to be shared by a wide range of serotypes, but the extent of the cellular lesions appears to be characteristic of individual virus strains.…”
Section: Potential Triggers Of ␤-Cell Autoimmunity and Type 1 Diabetesmentioning
confidence: 99%
“…The enterovirus Coxsackievirus B4 was considered of etiological significance in T1D because it leads to functional impairments and b-cell damage (42). Evidence suggests that human islet cells can sustain an enteroviral infection in patients with T1D.…”
Section: Discussionmentioning
confidence: 99%